Welfare Reform and Immigrant Fertility - Catalina Amuedo-Dorantes; Susan L. Averett; Cynthia Bansak (Institute for the Study of Labor (IZA), 2014)
Immigration policy continues to be at the forefront of policy discussions, and the use of welfare benefits by immigrants has been hotly debated. In 1996, Congress enacted welfare reform legislation (PRWORA), which denied the use of most means-tested assistance to non-citizens and lowered immigrant welfare dramatically. While Federal legislation imposed strict restrictions on eligibility for non-citizens, a number of states allowed previously eligible women to continue to receive benefits similar to those before 1996, whereas others imposed the new Federal cutbacks. Using data from the Current Population Survey (CPS) for the years 1994-2000, we examine whether immigrant women adjusted their childbearing in response to cutbacks in the generosity of welfare benefits at the state-level. Our findings suggest that non-citizen women, especially those of Hispanic origin, altered their fertility decisions in response to the legislation. In addition, they increased their labor force participation, possibly to obtain employer-sponsored benefits. Our results are robust to alternative definitions of our treatment and control groups and do not appear to be driven by pre-existing trends. Finally, we find no evidence that women who anticipated having children migrated to the more generous states. Overall, the results provide further evidence that immigrants respond to variation in state-level policies and provide insight into the potential impacts of comprehensive immigration reform, particularly the components related to the path to citizenship and access to public benefits.
Keywords: J13; I38; 330; immigration; fertility; welfare reform